Recommendations for the surgical treatment of endometriosis. Part 2: deep endometriosis - Keckstein, J; Becker, CM; Canis, M; Feki, A; Grimbizis, GF; Hummelshoj, L; Nisolle, M; Roman, H; Saridogan, E; Tanos, V; Tomassetti, C; Ulrich, UA; et al. (Oxford University Press, 2020)
STUDY QUESTION How should surgery for endometriosis be performed?